Peer-feedbacks based application in teaching speaking and students’ perception towards peer-feedbacks - Risa Triassanti; Christina Innocenti Tumiar Panggabean; Mansur Mansur (Journal of Applied Studies in Language, 2023)
Most of the students in EFL classes have less exposure and chances to speak with friends and colleagues in English. In the present study, students were situated on video. The peer feedback-based application was employed for guiding students to provide comments on peers' speaking performance. In order to investigate peer feedback, an online observation was conducted in the English education study program, online class. The online questionnaire was also done to recognize the students’ perceptions of peer feedback. The study results reveal some steps done in doing the peer-feedback-based application in terms of the learners' speaking aspects including pronunciation, grammar and vocabulary, and fluency. Moreover, it was found that the students can give feedback comprehensively to their peers. The perception of students toward peer feedback is positive and significantly helps students to improve their speaking ability. In conclusion, students have to think about their feedback before sending it to their peers. Future research should find the effectiveness of teacher feedback-based application and the correlation with the type of feedback.